2006
DOI: 10.1021/ja0658463
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride Ion Capture from Water with a Cationic Borane

Abstract: The reaction of the [Li(THF)4]+ salt of dimesityl-1,8-naphthalenediylborate with [Me2NCH2]I affords a borane (1-(Mes2B)-8-(Me2NCH2)-C10H6) which can be converted into a cationic borane [3]+ ([1-(Mes2B)-8-(Me3NCH2)-C10H6]+) by methylation with MeOTf. This cationic borane promptly complexes fluoride to afford the corresponding zwitterionic ammonium/fluoroborate 3-F (1-(Mes2FB)-8-(Me3NCH2)-C10H6). Cation [3]+ fails to react with chloride, bromide, and iodide indicating that fluoride complexation is selective. Str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
97
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 205 publications
(100 citation statements)
references
References 20 publications
2
97
0
1
Order By: Relevance
“…Recently there has been growing interest in designing hosts that are able to complex the fluoride ion in aqueous solution. [30,31] Attempts to study the ability of compound 2·H 2 O to capture sodium fluoride in water failed because of its rather limited solubility in this solvent. However, the fact that 2·H 2 O already contains water and that the acetonitrile was not specifically dried prior to use makes it likely that water will not preclude fluoride complexation by the organotin moiety.…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
“…Recently there has been growing interest in designing hosts that are able to complex the fluoride ion in aqueous solution. [30,31] Attempts to study the ability of compound 2·H 2 O to capture sodium fluoride in water failed because of its rather limited solubility in this solvent. However, the fact that 2·H 2 O already contains water and that the acetonitrile was not specifically dried prior to use makes it likely that water will not preclude fluoride complexation by the organotin moiety.…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
“…[4] Recently, receptors based on a strong and selective boron-fluoride ion interaction have been found to achieve highly efficient fluoride ion detection. [5] In particular, sterically hindered boryl groups such as dimesitylboryl and tridurylboryl moieties showed enhanced size-selectivity toward fluoride ions. [5b-f,i,k-l,p,r,6] Moreover, some of them exhibited protic media tolerance, which is very advantageous compared with other receptors.…”
mentioning
confidence: 99%
“…Studies of several groups have demonstrated that boron based receptors that are bidentate and cationic capitalize on both Coulombic and cooperative effects leading to a further enhancement of their F  affinity. Consequently, F  detection in aqueous media could be realized [37][38][39][40]. In order to recognize F  in water solution, Gabbaï et al [37][38][39][40] developed a number of cationic boranes (40-44 in Figure 12).…”
Section: Fluoride Detection In Aqueous Mediamentioning
confidence: 99%
“…Consequently, F  detection in aqueous media could be realized [37][38][39][40]. In order to recognize F  in water solution, Gabbaï et al [37][38][39][40] developed a number of cationic boranes (40-44 in Figure 12). These compounds were able to bind with F  in organic solvent/ water mixed solution with high sensitivity and selectivity.…”
Section: Fluoride Detection In Aqueous Mediamentioning
confidence: 99%
See 1 more Smart Citation